A Review of Unusual New Projectile Types. Issue 2 (June 2013) - Poulos, Christopher K.; Tlomak, Wieslawa
Specialty ammunition and projectile types may present a challenge to a forensic pathologist as they can alter the appearance of wounds and have unique structural components that can make interpretation of gunshot wound patterns more difficult. Although specialty projectiles have existed for years, several new projectile types have recently been developed. These include ammunition tailored around new hunting regulations, around new polymer usage, and around new handgun types that can fire both conventional ammunition and shotshells. In this article the authors will discuss known design and forensically relevant characteristics of some new ammunition types including the Hornady Critical Defense cartridges and shotshells, the Hornady Critical Duty cartridges, the Cor-Bon Glaser Pow'RBall cartridges, the Winchester PDX1 .410 shotshell, and the Winchester Blind Side shotshell.